1995
DOI: 10.2337/diab.44.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Trinucleotide Repeats at the rad Locus: Allele Distributions in NIDDM and Mapping to a 3-cM Region on Chromosome 16q

Abstract: A 10-allele polymorphism was identified in rad (ras associated with diabetes), a gene that is overexpressed in non-insulin-dependent diabetes mellitus (NIDDM) muscle. The polymorphism, designated RAD1, consists of a variable number of trinucleotide repeats (GTT and ATT) located in the poly(A) region of an intronic Alu sequence. Based on the number of GTT and ATT repetitions, the alleles can be grouped into four classes (I-IV). RAD1 allele frequencies were determined in 210 NIDDM patients and 133 nondiabetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…RAD1 encodes a protein that belongs to a class of small GTP binding proteins related to Ras, which was first identified as being overexpressed in skeletal muscle of patients with T2D (18). SNPs in RAD1 locus in skeletal muscle have been linked to T2D (34). Collectively, these data indicate that multiple pathways downstream of insulin receptor signaling are perturbed in IR-Mut myocytes and likely contribute to the metabolic defects observed in these patients in vivo.…”
Section: Discussionmentioning
confidence: 81%
“…RAD1 encodes a protein that belongs to a class of small GTP binding proteins related to Ras, which was first identified as being overexpressed in skeletal muscle of patients with T2D (18). SNPs in RAD1 locus in skeletal muscle have been linked to T2D (34). Collectively, these data indicate that multiple pathways downstream of insulin receptor signaling are perturbed in IR-Mut myocytes and likely contribute to the metabolic defects observed in these patients in vivo.…”
Section: Discussionmentioning
confidence: 81%
“…Although two larger human studies (3, 4) could not confirm a direct association between the Rad level and diabetes, Garvey et al (3) did find a positive correlation between the level of Rad in skeletal muscle and body-mass index or percentage of body fat. In addition, genetic studies in two of three different Caucasian populations found a possible association between trinucleotiderepeat polymorphism of the region of the Rad gene and type 2 diabetes (7,8,17), and in a Chinese population, a novel Rad gene polymorphism was found to be associated with an increased risk for type 2 diabetes when combined with obesity (18). At the cellular level, previous work by our laboratory has demonstrated a reduction of insulin stimulated glucose uptake in both cultured adipocytes and muscle cells overexpressing Rad, consistent with a role in insulin resistance (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although some subsequent studies (3,4) did not confirm this direct association between the Rad mRNA level and diabetes, other studies have shown that Rad is an insulin regulated gene in muscle (5) and that Rad overexpression inhibits glucose transport in muscle cells in culture (6). There is also a correlation between the level of Rad expression and obesity (3), and genetic analysis studies of two different populations found a possible association between trinucleotide-repeat polymorphism of the Rad gene and type 2 diabetes (7,8).…”
mentioning
confidence: 97%
“…Allele frequencies were determined in the 32 original family probands, 173 Joslin's patients with type 2 diabetes, and 181 nondiabetic control subjects by PCR, dot-blotting, and allele-specific hybridization. The recruitment of the type 2 diabetic individuals and nondiabetic control subjects has been previously described (20). The clinical features of these subjects are reported in Table A5, which can be found in an on-line appendix at www.diabetes.org/diabetes/appendix.htm.…”
Section: Type 2 Diabetes Locus On 12q15mentioning
confidence: 99%